1989
DOI: 10.1159/000116388
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Cerebral Angiopathy: Reversible Vasoconstriction Assessed by Transcranial Doppler Ultrasounds

Abstract: Postpartum cerebral angiopathy is a distinct reversible clinicoradiological syndrome which develops shortly after a normal pregnancy. It may belong to the poorly defined group of acute benign cerebral angiopathy, in which multisegmental narrowings of cerebral arteries are also reversible. In a 22-year-old woman with postpartum cerebral angiopathy, sequential transcranial Doppler ultrasounds showed that the flow disturbances began to improve 4 days after onset, and normalized 4 weeks later. A vasoconstriction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(78 citation statements)
references
References 12 publications
4
72
0
2
Order By: Relevance
“…First, our case series closely resembles, clinically and angiographically, similar case studies that have been reported in association with other disorders linked to reversible vasoconstriction. These include vasculopathy in the postpartum period (15)(16)(17)(18), vasculopathy associated with pheochromocytoma (19), and that associated with the use of sympathomimetic drugs (20 -32). In each of these examples, the clinical picture is characterized by similar angiographic findings, benign spinal fluid, and a monophasic course.…”
Section: Discussionmentioning
confidence: 99%
“…First, our case series closely resembles, clinically and angiographically, similar case studies that have been reported in association with other disorders linked to reversible vasoconstriction. These include vasculopathy in the postpartum period (15)(16)(17)(18), vasculopathy associated with pheochromocytoma (19), and that associated with the use of sympathomimetic drugs (20 -32). In each of these examples, the clinical picture is characterized by similar angiographic findings, benign spinal fluid, and a monophasic course.…”
Section: Discussionmentioning
confidence: 99%
“…TCD is a valid noninvasive and easily available tool that can be performed as many times as necessary to identify/quantify the severity of cerebral arterial vasoconstriction and monitor the response to treatment in follow-up. 3 We describe a case of a 41-year-old patient (gravida 5, para 1) with no complications in her current pregnancy. She was treated with norepinephrine for severe hypotension after uterine arterial disruption and cabergoline to prevent lactation after delivery.…”
Section: Letter By Martínez-martínez Et Al Regardingmentioning
confidence: 98%
“…Although the gold standard for diagnosis of PPA is digital subtraction angiography, TCD is a valid, noninvasive, and easily available tool that can be used as many times as necessary to identify/quantify the severity of the vasoconstriction as well as monitor the response to treatment on follow-up. 3 We used this method with the Lindegaard index to assess improvements and response to treatment.…”
Section: Letter By Martínez-martínez Et Al Regardingmentioning
confidence: 99%
“…Postpartum angiopathy, a reversible cerebral vasoconstriction syndrome, is a parsimonious diagnosis linking her headache, pregnancy, elevated CSF protein, MRI findings, and encephalopathy. 2,3 However, postpartum angiopathy typically follows delivery, rather than precedes it, and often presents with vomiting and/or seizures.…”
Section: Go To Section 3 Sectionmentioning
confidence: 99%